Localized 1H NMR measurements of gamma-aminobutyric acid in human brain in vivo. - Rothman, D L (1993)
Localized 1H NMR spectroscopy in conjunction with J editing was used to measure the concentration of gamma-aminobutyric acid (GABA) in the occipital lobe of four control human volunteers and four epileptic volunteers who were receiving the drug vigabatrin. The GABA concentration measured in four nonepileptic subjects was 1.1 +/- 0.1 mumol/cm3 of brain, which is in good agreement with previous values measured in surgically removed human cortex. A dose-dependent elevation of GABA concentration was measured in patients receiving the GABA transaminase inhibitor vigabatrin, with the maximum measured level of 3.7 mumol/cm3 of brain measured at the highest dose (6 g per day) studied. 1H NMR measurements of GABA in those patients receiving GABA-elevating agents such as vigabatrin will be of importance in establishing the relationship between seizure suppression and the concentration of brain GABA.